The Spirit of God Transforming Life - Chung, P. author. aut Link
XV, 195 p.
Keywords: By re-examining the central themes of Reformation theology, Chung clearly and carefully describes the fundamental shape of Reformation thinking and introduces the reader to what was and is at stake in the Reformation's insistence on the centrality of the Gospel.